Safety and Feasibility of Same-Day Discharge in Obese Patients Undergoing Laparoscopic Hysterectomy for Endometrial Intraepithelial Neoplasia and Malignancy [335]. (May 2015) - Katz Eriksen, Jennifer Leigh; Melamed, Alexander; Berkowitz, Ross Stuart; Horowitz, Neil S.; Muto, Michael George; Feltmate, Colleen Marie
Abstract : INTRODUCTION: Hysterectomy for endometrial cancer is increasingly performed by laparoscopic surgical technique. Same-day discharge is safe, cost-saving, and acceptable to patients undergoing laparoscopic hysterectomy, but concerns about increased perioperative risks in obese patients limit the utilization of same-day discharge in this population. We evaluated the risk of perioperative complications in obese patients undergoing laparoscopic hysterectomy for endometrial cancer or endometrial intraepithelial neoplasia in our institution during a period of rapid increase in the utilization of same-day discharge. METHODS: Single-institution retrospective cohort including all obese patients (body mass index [calculated as weight (kg)/[height (m)] 2 ] 30) undergoing laparoscopic hysterectomy for endometrial cancer or endometrial intraepithelial neoplasia between 2011 and 2013. RESULTS: A total of 388 patients were included. Those with class III obesity were younger than those with class I or II (58.4 compared with 63.0 years, P <.001) and less likely to have invasive endometrial cancer (80.9% compared with 88.7%, P =.04). Those with class III obesity were significantly more likely to undergo robot-assisted laparoscopy than those with class I or II obesity (57.5% compared with 18.6%, P <.001). The rate of same-day discharge increased significantly over the 3-year study period: for those with class I and II obesity from 18.6% to 65.5% and for those with class III obesity from 12.7% to 61.4% ( P <.001). During this period there were no significant differences in frequency of postoperative complications within 30 days of surgery, including readmission, unscheduled surgery, or infection ( P =.1 for all). CONCLUSION: Same-day discharge is safe and feasible for the majority of obese patients undergoing laparoscopic surgery for endometrial cancer and endometrial intraepithelial neoplasia.